Influence of Ca2+ or Na+ extraframework cations on the thermal dehydration and related kinetic performance of LSX zeolite. (December 2016) - Panezai, Hamida; Fan, Minghui; Sun, Jihong; Bai, Shiyang; Wu, Xia
Abstract: Nitrogen adsorption performances of low-silica type X zeolites (LSX) containing Na + or Ca 2+ ions were studied and compared with Li + ion, and their structural and thermal properties were investigated using various characterizations (XRD, TG-DTG, BET, XPS, SEM, TEM, and EDX with elemental mapping techniques). The kinetics of their thermal dehydration and decomposition was studied using thermogravimetry at three rates (5, 10, and 15 K/min) of linear increase of temperature under non-isothermal heating. Two model free procedures named, Kissinger, and Flynn–Wall–Ozawa (iso-conversional) and one model fitting method called Coats–Redfern based on single TG curves, as well as 41 mechanism functions were used. The kinetic parameters (apparent activation energy E, pre-exponential factor A and model) of the three phases for each sample obtained from the non-isothermal methods were then compared with the results from iso-conversional methods this showed that they strongly depend on the selection of appropriate mechanism function and the corresponding kinetic model from the perspective of crystal structure used. The results demonstrated that the E value obtained at low temperature was lower than that at high temperature, implying that the dehydration process of physisorbed water belongs to diffusion-based control, while decomposition of bonded water (chemisorbed) belongs to kinetic-based control at high temperature. These comparisons allow us to underline the strong effect of cations in association with water and their distribution in the micropores of LSX on the N2 adsorption performance. Graphical abstract: Highlights: Influence of Ca 2+ ion and water content on N2 adsorption of LSX was investigated. Dehydration mechanism in Ca-LSX was suggested. Kinetic models for dehydration procedure in Ca-LSX were proposed.